Comparative Evaluation of Hospital Inpatient Room Design against Regulations and Integrated Project Delivery (IPD) Principles - Irena Suryandari Fauziyyah; Suparwoko Suparwoko; Handoyotomo Handoyotomo (Program Studi Arsitektur, Fakultas Teknik, Universitas Katolik Parahyangan, 2025)
This study conducts a comparative evaluation of the inpatient room design in JIH Hospital Purwokerto and the Universitas Islam Indonesia Hospital (RSA UII) Yogyakarta in relation to the technical standards stipulated in the Decree of the Minister of Health Number HK.01.07/MENKES/1122/2022 on Technical Standards for Hospital Inpatient Rooms and the principles of Integrated Project Delivery (IPD). The study focuses on three central issues: the inadequacy of inpatient room dimensions, potential risks to patient safety and the limited interdisciplinary coordination during the design process. A comparative qualitative method was employed, combining direct observation, architectural document analysis, and regulatory review. The findings indicate that the inpatient rooms at JIH Hospital Purwokerto do not meet the minimum spatial requirements and exhibit suboptimal evacuation patterns, which may affect patient safety. In contrast, RSA UII demonstrates greater conformity to dimensional standards and better functional integration. The study also identifies that the absence of Building Information Modeling (BIM) in the design process contributes to reduced coordination among design professionals. Based on these findings, the study recommends design improvements that include meeting minimum spatial standards, separating clean and dirty zones, optimizing cross ventilation, and strengthening collaborative planning grounded in IPD principles and supported by BIM technology.